Ageing causes prominent neurovascular dysfunction associated with loss of astrocytic contacts and gliosis. (27th March 2017) - Duncombe, J.; Lennen, R. J.; Jansen, M. A.; Marshall, I.; Wardlaw, J. M.; Horsburgh, K.
Abstract : Aims: Normal neurovascular coupling, mediated by the fine interplay and communication of cells within the neurovascular unit, is critical for maintaining normal brain activity and cognitive function. This study investigated whether, with advancing age there is disruption of neurovascular coupling and specific cellular components of the neurovascular unit, and whether the effects of increasing amyloid (a key feature of Alzheimer's disease) would exacerbate these changes. Methods: Wild‐type mice, in which amyloid deposition is absent, were compared to transgenic amyloid precursor protein (APP) littermates (TgSwDI) which develop age‐dependent increases in amyloid. Baseline cerebral blood flow and responses to whisker stimulation were measured. Components of the neurovascular unit (astrocytes, end‐feet, pericytes, microglia) were measured by immunohistochemistry. Results: Neurovascular coupling was progressively impaired with increasing age (starting at 12 months) but was not further altered in TgSwDI mice. Aged mice showed reduced vascular pericyte coverage relative to young but this was not related to neurovascular function. Aged mice displayed significant reductions in astrocytic end‐feet expression of aquaporin‐4 on blood vessels compared to young mice, and a prominent increase in microglial proliferation which correlated with neurovascular function. Conclusions: Strategies aimed to restore the loss of astrocytic end feet contact and reduce gliosis may improve neurovascular coupling. Abstract : The neurovascular unit is important for maintaining the blood brain barrier and immune surveillance. Advancing age leads to dysfunction of the neurovascular unit with increased gliosis and alterations to astrocytic end feet with important implications for age‐related cognitive decline.